Does employee welfare affect corporate debt maturity?. Issue 5 (October 2019) - Boubaker, Sabri; Chourou, Lamia; Haddar, Marwa; Hamza, Taher
Abstract: This study examines the effect of employee well-being on the corporate debt maturity structure of U.S. firms. It hypothesizes that a firm's degree of commitment to employee welfare affects its debt maturity structure. Using a sample of 19, 347 firm-year observations over the period 1991–2014, we find evidence that firms with higher employee welfare scores prefer long-term debt over short-term debt. This relationship is more pronounced for firms operating in human-capital-intensive industries and firms with lower labor union-membership rate. Our findings are robust to endogeneity concerns and insensitive to the use of alternative regression methods, variable measurements, and sample compositions. This paper provides novel evidence on the role of employment policies and practices in explaining variations in debt maturity. Highlights: Examine the relationship between employee welfare and corporate debt maturity. Firms' commitment to employee welfare leads to the use of less short-term debt. This relation is more exacerbated for firms in labor-intensive firms. This relation is more exacerbated in less stringent labor union climate.